A bidding specification for Grid resources. (6th August 2009) - Vilajosana, X.; Marques, J.M.; Juan, A.; Krishnaswamy, R.
Utility computing and Grid are establishing themselves business models where resource providers invest in technology and software platforms. One of the most studied problems is that of efficient resource allocation. Computational efficiency is translated into economical efficiency creating incentives to resource providers to develop nearly optimal resource allocation frameworks. Auctions have proven their ability to do so. Besides, due to the heterogeneity of these environments, some new approaches adopt multiple different auctions to best fit each situation. Our work tries to homogenise scenarios where multiple market mechanisms are present, thus providing to bidders a well-defined bidding specification language that makes their bids independent of the auction mechanism used.